Degree of hydration and compressive strength of conditioned samples made of normal and blended cement system - Shafiq, N. (Springer, 2011)
In this paper; results of the degree of hydration of the pastes and the compressive strength of the 50 mm cubes prepared with the 100% cement and fly ash blended cement was determined. 24 hours after casting mortar cubes and the paste samples were cured for 28 days in the fog room. After 28 days curing; a set of 3 cubes and a paste sample was dried in the 100%, 75%, 65%, 40% and 12% ambient relative humidity at the constant temperature of 27oC. Drying conditions showed significant affects on the compressive strength and the degree of hydration. Highest compressive strength of 70 MPa was measured of mortar cubes dried in 100% RH; similarly 97% degree of hydration was determined for 100% cement samples dried in the 100% RH. For mortar cubes dried in 12% RH, the compressive strength was measured between 47 and 53 MPa. The similar paste samples showed the maximum degree of hydration as 81%.